ANALISIS KEBIASAAN MAKAN DAN PERTUMBUHAN IKAN KEPERAS (Cyclocheilichthys apogon) DI SUNGAI LETING DESA KEMUJA, KABUPATEN BANGKA SEBAGAI TAHAPAN DOMESTIKASI - Tiara Sari; Andi Gustomi; Okto Supratman; Okto Supratman (Akuatik: Jurnal Sumberdaya Perairan, 2020)
Freshwater fish is a part of aquatic biodiversity that has not been thoroughly exposed and become the potential that has not been fully utilized. Many attempts have been made to obtain freshwater fish, one of it is domestication. The domestication of freshwater fish aims to tame animals that live in the wild. This study aims to determine the composition of the food that became the eating habit of it fish, to determine the growth pattern and to analyze the relationship between the length interval and the composition of the food. This research was conducted in December 2019 - February 2020 at Sungai Lenting, Kemuja Village. Bangka Regency. The sample of Keperas fish was taken by using the purposive sampling method. Data collection is divided into 3 stations : upstream, mid-river and downstream. The results showed that Keperas fish is the omnivore. The biggest precentage of food composition in both males and females were Microstella norvegica with amount of index of preponderance were 21,36% and 26,13 respectively. The growth pattern of Keperas fish was Negative Allometric, but in February the male fish had a Positive Allometric growth pattern. The food indek based on the range of the length for males and females is dominated by zooplankton with the species was Microstella Norvegica